Cálculo y análisis de la huella de carbono de una empresa productora y exportadora de flores en La Sabana de Bogotá (2023)
In the present project, whose main objective was to calculate the carbon footprint produced by a company that produces and exports flowers in the Bogotá savannah, thus analyzing scopes 1, 2 and 3, the latter in regards to distribution, work was carried out hand in hand with the organization Rosas Tesalia S.A, located in the Bogotá savanna, specifically in the municipality of Madrid, Cundinamarca. Using two methodologies for the calculation, first, the Methodological Guide for measuring indicators in the Florverde Impact, Monitoring and Evaluation System, and second, the Green House Gas Protocol (GHG Protocol), the aforementioned objective was achieved. . This calculation gave a value of 7154.12 tons of CO2eq. At the end of the project, a correct identification of the sources of greenhouse gas (GHG) emissions was carried out, and from this, together with the calculation of the carbon footprint, different control, compensation or reduction actions were proposed. the same, in order to direct the company towards more sustainable production. These compensation or reduction actions were evaluated by the scoring method proposed by (Gutiérrez & Montoya, 2016) in “The carbon footprint as a tool to achieve sustainable production in a flower crop located in the Sabana de Bogotá – Colombia”.